Kekerasan Intelektual Dalam Islam (Telaah Terhadap Peristiwa Mihnah Mu’tazilah) - Fahruddin Faiz (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Religious violence is a term that covers phenomena where religion, in its  diversity, is either the subject or object of violent behaviour. Religious violence is, specifically, violence that is motivated by or in reaction to religious precepts, texts, or doctrines. Islam has been associated with violence in a variety of contexts, including Jihads (holy wars), violent acts by Muslims against perceived enemies of Islam, violence against women ostensibly supported by Islam's tenets, references to violence in the Qur'an, and acts of terrorism motivated and/or justified by Islam. Muslims, including clerics and leaders have used Islamic ideas, concepts, texts, and themes to justify violence. One among popular religious violence in Islamic History is mihnah (inquisition). To socialize Mu’tazilah teaching, Al-Ma’mun and his successors managed Mihnah or inquisition, that is the dispersion of this belief and teachings forcefully and even violently. As the ruler, Al Ma’mun thought that it was his duty to maintain the purity of the religion and the  truth enforcement in the state community. As described in this article, Mihna is a kind of intellectual violence conducted by Mu’tazilah and Al-Ma’mun as a kind of coalition between religion and politics.